Fulminant Encephalopathy with Marked Brain Edema and Bilateral Thalamic Lesions - Ando, Naoki; Okumura, Akihisa; Kobayashi, Satoru; Negishi, Yutaka; Hattori, Ayako; Okanishi, Tohru; Abe, Shinpei; Ikeno, Mitsuru; Igarashi, Ayuko; Saitoh, Shinji; Shimizu, Toshiaki (Neuropediatrics, 2014)
We encountered two children with acute encephalopathy associated with unique clinical manifestations. Both the patients had status epilepticus at onset and neuroimaging studies revealed marked brain edema and bilateral thalamic lesions. Although they were treated with steroids and immunoglobulin, their outcomes were very poor. A thermolabile variant of carnitine palmitoyltransferase II and an elevated interleukin-6 level in cerebrospinal fluid were observed in one patient each. The constellation of clinical and neuroimaging findings in our patients is apparently not consistent with any established subtype of acute encephalopathy/encephalitis.
Keywords: acute encephalopathy; brain edema; thalamic lesions